چلم نامہ “عصرِ حاضر کی عکاس - Dr. Rukhsana Baloch; Dr. Rubina Yasmeen; Dr. Sumaira Shafi (Khayaban - خیابان, 2022)
“Chilm Nama” is long poem by There is an ancient tradition of writing long poems consisting complete book. “Chilam Nama” is a long poem written by Muhammad Yousaf Papa. “Chilam” word is used in this poem in the meaning of flattering. Flattering is big curse in this world. Today, we have to face many difficulties is this world without flattering. Flattery is a defect that degrades the character of both the flatterer and the flatterer morally. This poem is a kind of reform works. It is a deep satire on those people who even they do not have any kind of ability, they can get big positions only by flattering, importation and harassment.